Student Perceptions of Facebook Marketing in Higher Educations: A Case Study of the University of Jaffna, Sri Lanka - Dilogini, S.; Laxman, P.G.H.M. (South Eastern University of Sri Lanka, 2025)
This study explores how Facebook marketing shapes student perceptions of Higher Education Institutions (HEIs), focusing on the state-owned University of Jaffna, Sri Lanka. While Facebook is a common global marketing tool for HEIs, its specific effectiveness and reception in state universities within developing nations remain underexplored. This research addresses that gap. A thematic analysis of interviews with 26 MBA students revealed six key themes. Findings highlight Facebook’s advantages: it is cost-effective, offers broad youth reach and fosters interactive communities among prospective students, current students and alumni. This access to peer insights and visual content directly influences application decisions. However, significant challenges were also identified, including content over-saturation, perceived credibility issues compared to official websites, algorithmic constraints on organic reach and risks from unmanaged negative feedback. While Facebook drives stronger general engagement than visually-focused platforms like Instagram or professionally-oriented networks like LinkedIn, it is less effective at reaching niche audiences such as international students. The study concludes that for state-owned HEIs in contexts like Sri Lanka, Facebook is a valuable yet limited tool. To maximize its potential, it must be integrated into a broader multi-platform strategy. Practical recommendations include creating engaging, credible content; using targeted ads to supplement organic reach; and proactively managing online reputation. This research offers original insights and actionable guidance for universities in developing nations to refine their social media marketing for improved student recruitment and engagement.
Keywords: Facebook marketing; Higher education institutions (HEIs); Student perceptions; Social media engagement; Sri Lanka; University branding